ANALISIS GIRDER PRATEGANG TERHADAP BEBAN PELAKSANAAN ANTARA METODE KONVENSIONAL DAN INOVATIF - taufiq rochman; sudarmanto -; fifil umam (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2019)
Implementation method plays a vital role in the world of construction because it is related directly to the project scheduling. In apply on implementation method, both sefety factor and effectiveness of work must be identified. The purpose of the analysis is to determine the behavior of the girder of a bridge implemented using innovative methods and to determine the safety factor during the implementation. The required data were the height of girder is 2.1m and width 0.7m. Referred to SNI 1725 Loading for bridges, and controlling structures reffered to SNI T-12-2004 (Concrete Structure Planning for Bridges). The analysis began by determining the geometry dimensions of the girder, STAADPro software was used for modelling and Microsoft Excel was for analyzing. The results of the analysis show that innovative method is safe to implement, the stresses that occur do not exceed the allowable stress; the safety factor shows all numbers more than 1, indicating if innovative method is safe. Keywords:Innovative modeling, Launching girder, Safe implementation, Safety factor